Islamic Resurgence in South Africa - Ahmad Khalil Aziz (International Institute of Islamic Thought, 1996)
The contemporary Islamic resurgence and spirit of pan-lslamism that are being experienced today throughout the world did not come about overnight. They are the results of two counterforces operative in any give period of time. On the one hand, there was the deconstructionist force, in the form of the colonial and imperial forces that sought to destroy the Islamic value system. On the other hand, there was the reconstructionist force of 'ulama haqq and the Sufi shaykhs, who served as the prime stiinulators of the reform impusle and of change in the religiopolitical outlook of Muslims throughout the world. Islam in South Africa South Africa has played a forceful role in maintaining Islam's dynamic position for about three centuries. The picturesque activities of the earlier ulama (in the broadest sense of the word)-particularly the Sufi shaykhs- and early imams laid the foundations for the contemporary Islamic resurgence in South Africa, as seen in the Musliin Youth Movement and such other da'wah movements as the Call of Islam. Past workers and present movements have been religiopolitical positivists and activists. From the outset, Muslims needed to reconstruct Islamic education and maintain the momentum of revivalism and resurgence activities. The Dutch East India Company and English East India Company: A Deconstructionist Force The East India Company refers to any of a number of commercial enterprises formed in Western Europe during the seventeenth and eighteenth centuries to further trade with the East Indies. These companies were given charters by their respective governments to acquire territory wherever they could and to exercise therein various governmental functions, including legislation, the issuance of currency, the negotiation of treaties, the waging of war, and the administration of justice ...